Mouse redox histology using genetically encoded probes - Fujikawa, Yuuta; Roma, Leticia Prates; Sobotta, Mirko Christoph; Rose, Adam J.; Berriel Diaz, Mauricio; Locatelli, Giuseppe; Breckwoldt, Michael O.; Misgeld, Thomas; Kerschensteiner, Martin; Herzig, Stephan; Müller-Decker, Karin; Dick, Tobias P. (Science signaling, 2016)
Preserving the redox state - Depending on the context, reactive oxygen species (ROS), such as hydrogen peroxide, function as cellular signals of redox state or cause tissue damage. Monitoring ROS in tissues from animals expressing genetically encoded ROS reporters is challenging because the methods for preparing the samples destroy the signal from the reporters. Fujikawa et al. identified a chemical processing method for thin tissue sections that “locked” the state of the redox biosensors without reducing their fluorescence. Furthermore, this method could be combined with immunofluorescence. Thus, this chemical methodology preserves the redox states of biosensors inside cells, tissues, and whole organisms, providing a much needed approach for studying pathologic and physiologic ROS signaling. - Mapping the in vivo distribution of endogenous oxidants in animal tissues is of substantial biomedical interest. Numerous health-related factors, including diet, physical activity, infection, aging, toxins, or pharmacological intervention, may cause redox changes. Tools are needed to pinpoint redox state changes to particular organs, tissues, cell types, and subcellular organelles. We describe a procedure that preserves the in vivo redox state of genetically encoded redox biosensors within histological tissue sections, thus providing “redox maps” for any tissue and comparison of interest. We demonstrate the utility of the technique by visualizing endogenous redox differences and changes in the context of tumor growth, inflammation, embryonic development, and nutrient starvation. - A cryogenic chemical processing method maps the redox state at the cellular and subcellular level in tissue sections. - A cryogenic chemical processing method maps the redox state at the cellular and subcellular level in tissue sections.